Delayed sleep-wake rhythm is associated with cognitive dysfunction, social dysfunction, and deteriorated quality of life in patients with major depressive disorder - Takaesu, Yoshikazu; Kanda, Yuta; Nagahama, Yu; Shiroma, Ayano; Ishii, Miho; Hashimoto, Tasuku; Watanabe, Koichiro (Frontiers in Psychiatry, 2022)
Background The delayed sleep-wake phase is commonly observed in major depressive disorder (MDD) and thought to be associated with functional impairments. This study aimed to evaluate the relationship between the delayed sleep-wake phase, cognitive dysfunction, social dysfunction, and quality of life in patients with MDD. Methods This cross-sectional design included 33 outpatients with MDD. Objective sleep-wake rhythm was assessed by actigraphy. Functional impairments were evaluated by the Japanese version of the Brief Assessment of Cognition in Schizophrenia (BACS-J), World Health Organization Disability Assessment Schedule (WHO-DAS), and Euro QOL 5 dimensions (EQ5D). Results Actigraphic assessment of the delayed sleep-wake phase (midpoint of sleep) was significantly correlated with the composite score of the BACS-J (r=-0.489, p=0.010), WHO-DAS score (r=0.466, p=0.014), and EQ5D score (r=0.472, p=0.013). No significant correlation was found between the other actigraphic sleep parameters (sleep latency, total sleep time, and sleep efficiency) and functional impairments. Conclusions Our study’s results suggested that the delayed sleep-wake phase is associated with cognitive dysfunction, social dysfunction, and deteriorated quality of life in patients with MDD. Clinicians should pay attention to the sleep-wake rhythm in patients with MDD in clinical settings.